Internal Migration of Ethno‐national Minorities: The Case of Arabs in Israel. (29th November 2012) - Cohen, Nir; Czamanski, Daniel; Hefetz, Amir
Abstract: Recent scholarship emphasizes differences among ethnic groups' internal migration patterns. Yet, with few exceptions, research has focused on the Anglo‐American world, neglecting experiences from other regions. This paper is part of a larger research project that studies mobility among the Arab minority in Israel and its driving forces. In this paper we examine patterns of internal migration by analysing the propensity to migrate as well as migrants' individual and social characteristics. First, we survey the theoretical backdrop that is suggested by recent geographic literature on internal migration among ethnic and racial minorities, including native groups. Second, we contextualize the group studied, providing necessary background information on the political, socio‐economic and demographic conditions of Arabs in Israel. We briefly discuss attributes that are – or have been – potential hindering factors to Arab mobility in the Jewish state. Finally, we analyse 1995 national census data at the micro scale and provide a basis for future explanations of the phenomenon. We conclude by outlying some future directions in the study of internal migration of minorities in Israel.